The Islamic Environmentalism in Eco-Pesantren Initiatives: Integrating the Sustainable Development Values in Islamic Boarding School - Anabarja, Sarah; Safril Mubah, Ahmad (Journal of International Relations on Energy Affairs, 2021)
The potential of Islamic environmentalism initiatives has been emerging in Indonesian Muslim society. The inclusion of sustainable development ideas into Islamic values has raised an increasing initiative of ‘Eco-Pesantren’. Following the numerous programs relating to Sustainable Development Goals (SDGs) in the country, the ‘Eco-Pesantren’ undertake the ideas by introducing environmental sustainability in their curriculum. This initiative is widely popular after some Islamic boarding schools or ‘pesantren’ in Java Island have successfully performed the value of sustainable development in their learning process. It is evident that sustainable development ideas are not the opposite of Islamic values, and the Islamic way of life can contribute to the environmental vision of Sustainable Development Goals (SDGs). This article analyses the practice of sustainable development from an Islamic point of view by focusing particularly on environmental issues. To describe the ‘Eco-Pesantren’ programs, this article is divided into three sections. First, explaining sustainable development from Islamic perspectives. Second, portraying the growth of Islamic environmentalism in Indonesia and ‘Eco-Pesantren’ initiatives and the challenges faced by those initiatives. Finally, the conclusion of this study.